An Exploration of Visual Literacy through Pictures in Developing English Reading Comprehension for Elementary Students - Mazta, Swati (THE PRIMARY TEACHER, 2018)
This paper attempts a small-scale understanding of visual literacy through pictures in developing English reading comprehension for elementary students. It is based on the theory of language development through pictures, that if used effectively in the classroom might aid to develop English reading comprehension among elementary learners. During the teaching-learning process, the possible ways of using some factors of pictures are discussed that might help to improve learners English reading comprehension.